Self-efficacy and strategy use in the multi-variate model of motivation for English language learners in Iran / Masoomeh Khodadad - Masoomeh, Khodadad (2016)
Many studies, including the ones based on Gardner’s Socio-Educational Model, have indicated the influence of motivation on foreign or second language success (Tremblay and Gardner, 1995; Zairi, 1996; Kam, 2006; Bernaus and Gardner, 2008; Sayadian and Lashkarian, 2010). However, less attention has been given to the combination and interaction of particular factors that might potentially affect L2 learning. These variables as related to individual differences among learners, might be motivational (contributing to motivation) or non-motivational (promoted by motivation). Using two of the potentially individual difference constructs namely, self-efficacy and strategy use, this study aimed at investigating how these factors fit into Gardner's (2001) model and what their possible association might be since little empirical research has been conducted on the interactions and relationships of variables such as motivation, self-efficacy, strategy use, and learning. In order to develop a conceptual model, this study aimed to investigate and test a modified form of Gardner's (2001) socio-educational model of second/foreign language learning (updated in 2003), given that it is one of the most dominant and comprehensive models of second/foreign language learning, accounting for motivation in relation to other factors such as strategy use as well as other social, individual, and contextual aspects. This study aimed to find the causal interrelations among some individual difference variables namely, attitudes toward the learning situation, integrativeness as exogenous, motivation, strategy use, self-efficacy as mediating, and English language achievement as endogenous variables. 240 intermediate learners of English as a foreign language at the Iran Language Institute (ILI) participated in this study. Three questionnaires (the Attitude Motivation Test Battery [AMTB], the Self-Efficacy Questionnaire [SEQ], and the Strategy Inventory for Language Learning [SILL]) were administered to the participants to measure their language learning motivation, self-efficacy and strategy use respectively. The data were analyzed through the SEM (Structural Equation Modelling) research method which examines interrelated dependence and multiple relations in a single model with path coefficients. The software used for SEM was AMOS. The results of the SEM analysis showed a consistency between the hypothesized model and the collected data. The hypothesized model demonstrated good fit indices within the thresholds used as criteria of good fit. With the exception of attitudes toward the learning situation that did not show significant direct influence on strategy use and English achievement, (this was also the case in Gardner's 1997and 2000 studies), all the other paths in the model were significant. Findings indicated significant causal positive relationships between attitudes toward the learning situation and motivation, integrativeness and motivation, attitudes toward the learning situation and self-efficacy, self-efficacy and motivation, motivation and strategy use, and self-efficacy and strategy use. Results indicate that in order to have better strategy users, learners' self-efficacy and motivation should be improved. Furthermore, the findings reveal that integrativeness, self-efficacy, and motivation showed both significant direct and indirect positive influences on English language achievement. Learning strategy use also positively and directly affected English achievement. Based on the findings of the study, pedagogical implications for foreign language education are further discussed.